2020
DOI: 10.1152/ajpendo.00150.2020
|View full text |Cite
|
Sign up to set email alerts
|

Biological plausibility for interactions between dietary fat, resveratrol, ACE2, and SARS-CoV illness severity

Abstract: Horne JR, Vohl MC. Biological plausibility for interactions between dietary fat, resveratrol, ACE2, and SARS-CoV illness severity. The angiotensin converting enzyme-2 (ACE2) cellular receptor is responsible for the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), thus impacting the entrance and clearance of the virus. Studies demonstrate that upregulation of ACE2 has a protective effect on SARS-CoV-2 illness severity. Moreover, animal studies demonstrate that dietary intake can mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…Resveratrol is a polyphenol belonging to the group of stilbenes, naturally found in red wine, berries, grapes, nuts, and other foodstuffs. Horne et al (2020) reviewed the biological interaction between resveratrol and the ACE2 receptor described in four studies that have been published to date [48]. As explained in the Introduction section, SARS-CoV-2 uses the ACE2 receptor to enter the…”
Section: Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol is a polyphenol belonging to the group of stilbenes, naturally found in red wine, berries, grapes, nuts, and other foodstuffs. Horne et al (2020) reviewed the biological interaction between resveratrol and the ACE2 receptor described in four studies that have been published to date [48]. As explained in the Introduction section, SARS-CoV-2 uses the ACE2 receptor to enter the…”
Section: Resveratrolmentioning
confidence: 99%
“…Resveratrol is a polyphenol belonging to the group of stilbenes, naturally found in red wine, berries, grapes, nuts, and other foodstuffs. Horne et al (2020) reviewed the biological interaction between resveratrol and the ACE2 receptor described in four studies that have been published to date [48]. As explained in the Introduction section, SARS-CoV-2 uses the ACE2 receptor to enter the mammalian cells, as well as the transmembrane protease serine 2 (TMPRSS2), involved in the viral spike-(S) protein cleavage, which in turn mediates the fusion of virus and cellular membranes necessary for viral entry (Figure 1).…”
Section: Resveratrolmentioning
confidence: 99%
“…A recent meta-analysis indicated that resveratrol may improve cardiometabolic status and alleviate certain risk factors for cardiovascular disease, including insulin resistance and elevated cholesterol levels ( 62 ). Furthermore, previous studies demonstrated that resveratrol can deactivate the renin-angiotensin system ( 63 , 64 ) and have a protective role by upregulating ACE2 ( 65 ). Interestingly, as the recent report suggested, resveratrol can be a promising anti-COVID-19 drug candidate, likely acting through interference with the viral spike protein function ( 66 ).…”
Section: Beneficial Effects Of Dietary Polyphenols In Covid-19 Managementioning
confidence: 99%
“…In this context, epidemiological and animal food intervention studies have established a solid association between the consumption of polyphenol-rich foods or beverages and their preventive influence on complex diseases, including insulin resistance (IR) [ 5 , 6 , 7 , 8 ], type 2 diabetes (T2D) [ 9 , 10 , 11 , 12 ], obesity [ 5 , 9 , 13 , 14 , 15 , 16 ], cardiovascular diseases (CVD) [ 17 , 18 , 19 , 20 , 21 , 22 ], neurodegenerative disorders [ 23 , 24 , 25 , 26 ], and cancer [ 22 , 27 , 28 , 29 ]. Recently, polyphenols have also been suggested as plausible adjunctive therapeutic agents for the COVID-19-induced inflammatory storm [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%